2021
DOI: 10.1186/s12879-021-06580-z
|View full text |Cite
|
Sign up to set email alerts
|

Multifoci and multiserotypes circulation of dengue virus in Senegal between 2017 and 2018

Abstract: Background Dengue fever is a mosquito born disease associated with self-limited to life threatening illness. First detected in Senegal in the nineteenth century, and despite its growing incidence this last decade, significant knowledge gaps exist in our knowledge of genetic diversity of circulating strains. This study highlights the circulating serotypes and genotypes between January 2017 and December 2018 and their spatial and temporal distribution throughout all regions of Senegal. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
49
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(56 citation statements)
references
References 52 publications
5
49
2
Order By: Relevance
“…20 Since 2017 to date recurrent dengue outbreaks with co-circulation of many serotypes (DENV-1-3) are reported in Senegal. 21 According to data from WHOCC for arboviruses and hemorrhagic fever viruses, DENV-2 is continuously circulating in Senegal since 2014 (unpublished data); interestingly during all reported outbreaks since 2017, DENV-2 was identified as the dominant serotype only during epidemics in Rosso in 2018 (Northern Senegal). 32 Knowing that determinants of DENV fitness, pathogenesis, and disease outcome are multifactorial, our present study results revealed the circulation of DENV-2 strains belonging to two different clades of DENV-2 cosmopolitan genotype in Senegal in 2018.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…20 Since 2017 to date recurrent dengue outbreaks with co-circulation of many serotypes (DENV-1-3) are reported in Senegal. 21 According to data from WHOCC for arboviruses and hemorrhagic fever viruses, DENV-2 is continuously circulating in Senegal since 2014 (unpublished data); interestingly during all reported outbreaks since 2017, DENV-2 was identified as the dominant serotype only during epidemics in Rosso in 2018 (Northern Senegal). 32 Knowing that determinants of DENV fitness, pathogenesis, and disease outcome are multifactorial, our present study results revealed the circulation of DENV-2 strains belonging to two different clades of DENV-2 cosmopolitan genotype in Senegal in 2018.…”
Section: Discussionmentioning
confidence: 99%
“…20 Since then, dengue was considered endemic in Senegal, with a regular shift in circulating serotypes leading to recurrent epidemics. 21,22 In more recent years, we observed an increased incidence of dengue characterized by multifoci and the co-circulation of several serotypes. 21 Interestingly, viral endemicity may facilitate the accumulation of genetic diversity and could be linked to disease spread, severity, and outcomes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Dengue is hyperendemic (Dieng et al, 2021) in Senegal and this is known to be associated with a cyclic behaviour of serotype replacement leading to periodic epidemics (Laiton-Donato et al, 2019). Since 2017 a growing dengue incidence is noticed in Senegal with multifoci and multiserotypes circulation (Dieng et al, 2021).…”
mentioning
confidence: 99%
“…Dengue is hyperendemic (Dieng et al, 2021) in Senegal and this is known to be associated with a cyclic behaviour of serotype replacement leading to periodic epidemics (Laiton-Donato et al, 2019). Since 2017 a growing dengue incidence is noticed in Senegal with multifoci and multiserotypes circulation (Dieng et al, 2021). Interestingly, endemic behaviour may facilitate accumulation of genetic diversity and could be linked to disease spread, severity and outcomes (Laiton-Donato et al, 2019).…”
mentioning
confidence: 99%